IMPLEMENTATION OF PUBLIC COMMUNICATION STRATEGY IN IMPROVING RELATIONS IN THE ORGANIZATIONAL ENVIRONMENT OF KADIN BALI - Damayanti, I Gusti Agung Ayu Maha Dewi; Arlita, I G. A. Desy (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The increase in business actors that is happening today provides many significant changes for the community, technological advances not only help business actors in expanding their business but can also simplify the business marketing process anytime and anywhere. The role of business actors in maintaining consistency and increasing innovation in developing businesses can have a positive impact on increasing economic growth. The number of business actors who are active in business and varied in developing the business created, the expansion of the business market will increase. The purpose of this service is carried out by the author to find out the public communication strategy to improve relations in the Balinese Kadin organizational environment. The method that the author uses in this service is the mentoring method in the form of direct participation. Through this service, it is hoped that it can provide benefits, especially in the organizational environment of the Bali Chamber of Commerce in improving their relationships, so that the business development process with business actors can run well.